Working from Home and the Willingness to Accept a Longer Commute - Duco de Vos; Evert J. Meijers; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
It is generally found that workers are more inclined to accept a job that is located farther away from home if they have the ability to work from home one day a week or more (telecommuting). Such findings inform us about the effectiveness of telecommuting policies that try to alleviate congestion and transport related emissions, but they also stress that the geography of labour markets is changing due to information technology. We argue that estimates of the effect of working from home on commuting time are biased downward because most studies ignore preference based sorting (self-selection): workers who dislike commuting, and hence have shorter commutes, might also be more likely to work from home. In this paper we investigate to what extent working from home affects the willingness to accept a longer commute and we control for preference based sorting. We use 7 waves of data from the Dutch Labour Supply Panel and show that on average telecommuters have a 50 percent higher marginal cost of one-way commuting time, compared to non-telecommuters. We estimate the effect of telecommuting on commuting time using a fixed-effects approach and we show that preference based sorting biases cross-sectional results 27-28 percent downwards. Working from home allows people to accept 5.7 percent longer commuting times on average, and every additional 8 hours of working from home are associated with 3 percent longer commuting times.
Keywords: J32; R11; R41; 330; telecommuting; commuting time; job search; job mobility; labour market area